The human body : concepts of anatomy and physiology - Wingerd, Bruce D. (Wolters Kluwer/Lippincott Williams & Wilkins, 2014)
This book helps encourage learning through concept building, and is truly written with the student in mind. Learning Concepts divide each chapter into easily absorbed subunits of information, making learning more achievable. Since students in a one-semester course may have little experience with biological and chemical concepts, giving them tools such as concept statements, concept check questions, and a concept block study sheet at the end of each chapter help them relate complex ideas to simple everyday events. The book also has a companion Student Notebook and Study Guide (available separately) that reinvents the traditional study guide by giving students a tool to help grasp information in class and then reinforce learning outside of class